World atlas : slide and discover - Green, Jen (San Diego, CA, Silver Dolphin., 2012)
"Globe-trotters can embark on a unique adventure as they learn about the world's various cultures and composition, and how they work together--or sometimes don't. The six sophisticated slide-and-discover windows of this atlas offer a comprehensive view of the world's cultures and topography, continent by continent. Beautifully illustrated, and full of facts alongside stunning photographs of dramatic landscapes, wildlife, cities, and famous people, explore the amazing diversity of people and life within each country. Learn all sorts of fascinating things, like the earth's role within the solar system, the various climates of the world, what's inside Earth's core, maps and population distribution, world economies, natural wonders, early civilizations, and so much more. Also, find out for each continent how many countries it contains, its population, and which country is largest, smallest, has the longest river, is most densely populated, contains the highest peak, and much more."--B & N
Keywords: Atlas